On the Dynamics of a Harvested Tri-trophic Food Chain Model with Alternative Food Source - Guin, Lakshmi Narayan; Pal, Sarmistha; Sambath, Muniyagounder (Journal of Applied Nonlinear Dynamics, 2026)
A mathematical model addressing the phase transition scenario from stability to chaos in a three-species food chain model with alternative food source is presented in this research manuscript. The biological phenomenon of diverse solution trajectory formation has been uncovered here in terms of coupled nonlinear ordinary differential equations through positive initial conditions. The present paper is mainly focused on the existence and stability of coexistence equilibrium point as obtained by the system parameters and the interpretation of the result in terms of their possible ecological implications. The dynamics of the model reveal chaotic long-term behaviour over a broad range of parameters. The existence of a strange attractor and computation of the largest Lyapunov exponent also exhibit the presence of chaotic dynamics of our model. The final numerical simulations verify the correctness of our theoretical analysis.